Estimates of recharge of bauru aquifer system in a watershed surrounding the city of Uberaba - MG - Campos, José Cláudio Viégas (2021)
The Bauru Aquifer System (Sistema Aquífero Bauru - SAB) is a predominantly phreatic aquifer, with a large territorial extension, covering part of the states of Minas Gerais, São Paulo, Paraná, Goiás and Mato Grosso do Sul. In the region of the Triângulo Mineiro, although little studied, the SAB plays an important role in fully or partially meeting the demands for public water supply in several cities, in addition to contributing to the maintenance of river flows during the dry season. One of the main parameters to be evaluated for the management of an aquifer unit is its recharge rate, and in this sense, this paper presents estimates of recharge in the SAB, for the period from August 2016 to July 2019, in a watershed with 1.4 km2 area, around the city of Uberaba. Three methods were used to determine the recharge: The Climatic Water Balance (CWB) method based on precipitation and actual evapotranspiration data provided by the local weather station, the Water Table Fluctuation (WTF) method using 11 piezometer data on study area and the method supported by remote sensing data from the Gravity Recovery and Climate Experiment (GRACE) satellite system. The CWB method indicated a potential annual average recharge of 902 mm for the study period and the method with GRACE data indicated an average annual recharge of 517 mm. The potential recharge calculated by the CWB method was used as a reference to determine the maximum allowable value for the specific yield to be used in the WTF method. For the WTF method, a range of specific yield for the SAB was adopted from 0.05 to 0.09, the average values of the annual recharge varied from 302 to 541 mm. Although studies on the assessment of groundwater resources using GRACE data are normally applied on global/regional scales, the values obtained from average annual recharge were convergent with the WTF method.